Functions of English language in the Linguistic Landscape of Vilnius - Daraškienė, Inga (Taikomoji kalbotyra, 2024)
Globalization has made English one of the most widely spoken languages in the world. It has become the language code of choice for international communication and plays an important role in various sociolinguistic contexts, such as public or globalized spaces (Pennycook 2010). As a result, English is the most frequently studied object in linguistic landscape studies (Gorter and Cenoz 2023: 252). Examining the use of English in public spaces is relevant because it not only helps to assess the extent to which English is used in various sociolinguistic contexts but also reflects its prestige, power, and socioeconomic values, as well as its relationship with other languages. This paper analyses the functions of the English in the linguistic landscape of Vilnius, exploring how these functions differ depending on the discourse type. An analysis of 861 signs revealed the presence of English in the following discourses: commercial, cultural, street art, infrastructural, public service, tourism, COVID-19, protest, sports, regulatory, political, and health promotion. The findings indicate that English mainly performs an informative function – 63.8% of cases. In certain discourses – public service, COVID-19, and regulatory – English plays an exclusively informative role. Conversely, the symbolic use of English is observed approximately three times less frequently, primarily in the street art and sports discourses, where it accounts for 91.9% and 46.1% of cases, respectively. The study also examines whether the functions of English differ between monolingual and multilingual signs. The analysis shows that the informative function of English is more prominent in multilingual signs, while its symbolic function is more frequent in monolingual signs where English is the sole language. These findings suggest that English occupies a lingua franca role in Vilnius’s linguistic landscape. On the other hand, qualitative analysis shows that English is often influenced by the local Lithuanian language, both in its informative use and when chosen for its prestige, international appeal, or other symbolic powers.